Strategies for the Improvement of Forest Tree Species - some Cardinal Principles - Mehra, P. N. (Indian Forester, 1992)
Hyhridisation, recombination of gene of the compatible races and provenances followed by selection has heen suggested for softwoods and some of the hardwoods like Oaks, Laurels, Walnut, Maples, Champak, Albizias, Dalbergias and Xylias. To improve timber species like Teak, Sal, Sandalwood, Red Sanders, Walnut and Albizias hybridisation has been suggested between different ecological and geographical races. Polyploidy has been suggested for Morus, Canarium, Magnolia, Eugenia, Betula, Terminalia and Salix. Mass multiplication of such elites can be raised either through rooting of cuttings or tissue culture technique for planting mixed culture forest, simulating what exists in natural forest.